About the cognitive and contradictions environmental universe - Autova, G.M.; Kazachenok, V.V.; Mukashev, K.M. (Recent Contributions to Physics, 2020)
Without science in modern society, its intellectual and industrial power, the security of the state, is impossible. Science has become an important criterion for the civilization and culture of nations. Scientific and technical development is the main trend of historical progress at the turn of the XX-XXI centuries. But the attitude towards science is twofold. The first direction expresses confidence in science. It is recognized as one of the main values ​​of society and the dominant factor in the development of mankind. Proponents of the second direction criticize science for mistakes, see it as the main cause of crisis, environmental and social global problems. They believe that science is limited in its ability to solve the main and acute problems of social development. The roots of both directions have an objective basis. Therefore, today science is perceived in society ambiguously: on the one hand, with trust, hope and optimism, and on the other, with distrust and pessimism. But it is obvious that science cannot do without society in the 21st century. In light of this, the problems discussed and raised within the framework of this work did not arise from scratch and reflect the own views of its authors.